A Trip to the Unique Animal World of the "Central Kyzylkum" National Nature Park - Toshbotirovich, Khakimov Uktam; Uktamovich, Adilov Sobit; Kamolboyevich, Mamanazarov Jaloliddin; Azimboyevich, Kodirov Sobirjon (American Journal of Biology and Natural Sciences, 2024)
The article provides a brief description of some of the rare and endangered fauna in the territory of the Central Kyzylkum National Park. However, in order to preserve biodiversity, reserves, special reserves, biosphere reserves, national nature parks, nurseries, natural monuments have been established in our country to protect rare and endangered animals, to preserve and reproduce those that are in danger of extinction.